2001
DOI: 10.1097/00005373-200102000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Clinically Significant Blunt Cardiac Trauma: Role of Serum Troponin Levels Combined with Electrocardiographic Findings

Abstract: The combination of ECG and cTnI identifies reliably the presence or absence of Sig-BCT. Patients with an abnormal ECG and cTnI need close monitoring for at least 24 hours. Patients with a normal admission ECG and cTnI can be safely discharged in the absence of other injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
129
0
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(144 citation statements)
references
References 29 publications
7
129
0
7
Order By: Relevance
“…Cardiac troponins are most specifi c amongst conventional markers as they differ from the skeletal isoform by a unique aminoterminal sequence of 31 amino acids never expressed by skeletal muscle [43]. Cardiac troponin-I has shown maximum sensitivity (23-100%) and specifi city (85-97%) in detecting clinically signifi cant BCI [34][35][36][37][38][39][40][41][42][43][44][45][46]. Velmahos et al [47] concluded that, 100% negative predictive value was reached on combining ECG with troponin-I at 8 hours.…”
Section: Cardiac Markersmentioning
confidence: 99%
“…Cardiac troponins are most specifi c amongst conventional markers as they differ from the skeletal isoform by a unique aminoterminal sequence of 31 amino acids never expressed by skeletal muscle [43]. Cardiac troponin-I has shown maximum sensitivity (23-100%) and specifi city (85-97%) in detecting clinically signifi cant BCI [34][35][36][37][38][39][40][41][42][43][44][45][46]. Velmahos et al [47] concluded that, 100% negative predictive value was reached on combining ECG with troponin-I at 8 hours.…”
Section: Cardiac Markersmentioning
confidence: 99%
“…Однако перечисленные методы диагностики ушиба сердца, в том числе, определение уровня энзимов в плазме крови, элект рокардиография, эхокардиография, компьютерная томография, радионуклидная ангиография, либо характеризуются невысокой чувствительностью, либо не являются специфичными, либо чрез вычайно инвазивны и не относятся к рутинным [22][23][24][25].…”
unclassified
“…Так, по данным изучения кардиоспецифического изофермента миофибриллярной фракции креатинфосфоки назы, распространенность ушиба сердца составляет 15-24% [19,20,25], по данным чреспищеводной эхокардиографии -27-56% [43], по данным ЭКГ исследования -29-56% [21,25,26]. По результатам вскрытия, гистологическое под тверждение ушиба сердца получают менее чем в 50% случаев травмы груди [8].…”
unclassified
“…), а также клинические признаки (боль в обла сти сердца, артериальная гипотензия и др. ), либо характеризуются невысокой чувствительностью, либо не являются специфичными, либо чрезвычай но инвазивны и не относятся к рутинным [3,6,7]. Не является исключением и электрокардиографи ческое исследование -чувствительность метода составляет 40-50% [8,9].…”
unclassified
“…Не является исключением и электрокардиографи ческое исследование -чувствительность метода составляет 40-50% [8,9]. Однако ЭКГ исследова ние однозначно признается в качестве наиболее доступного и достаточно информативного (т. е. скринингового) метода для пациентов с тупой травмой груди [7,[10][11][12][13][14][15]. Кроме того, большинст во авторов считают его пригодным для выявления пациентов с риском развития поздних сердечных осложнений (фатальные аритмии, внезапная смерть и др.)…”
unclassified